A 13-Year Retrospective Study on Toxic Alcohol Poisoning in Middle Urals, Russia - Konstantin M. Brusin; Roman O. Nekhoroshkov (Asia Pacific Journal of Medical Toxicology, 2015)
Background: Toxic alcohol poisonings are responsible for high mortality and morbidity in Russia. This study was aimed to evaluate the trends of harmful ethanol (EtOH) drinking as well as methanol (MeOH), isopropanol (IPA) and ethylene glycol (EG) poisonings in the Middle Urals region of Russia. Methods: In this retrospective study, the medical records of patients poisoned with MeOH, IPA and EG as well as those with harmful heavy EtOH drinking admitted to Regional Poison Treatment Center in Yekaterinburg during the period of 2002 to 2014 were reviewed. Results: During this 13-year period, 17482 patients with acute poisoning (due to various toxic agents) were admitted, which 2244 of them (12.8%) were due to alcohol poisoning. Of all patients with acute poisoning, 502 cases died which 61 of them (12.2%) were due to alcohol poisoning. Most of the alcohol poisoned patients were men (1658, 73.9%). The male proportion of EG poisoned patients was higher than poisoned patients with other types of alcohol. Harmful EtOH drinking constituted the majority of alcohol poisoning cases (2076, 92.5%). Patients with EG poisoning were relatively older while patients with heavy EtOH intake were significantly younger (P < 0.001). The highest mortality rate (35.9%) was seen in patients with EG poisoning. During this period, heavy EtOH drinking had a slight increasing trend and MeOH poisoning had a sharp increasing trend. On the other hand, IPA poisoning had a constant trend and the trend of EG poisoning was decreasing. The majority of MeOH and IPA poisonings were due to ingestion of surrogate alcohols. Conclusion: Particular attention of health authorities should be directed towards alcohol drinking prevention measures as well as production and availability of surrogate alcohols in the community.